A New Model of Work Role Performance: Positive Behavior in Uncertain and Interdependent Contexts - Griffin, Mark A.; Neal, Andrew; Parker, Sharon K. (Academy of Management Journal, 2007)
We propose that interdependence in a work context determines to what extent work roles are embedded within a broader social system and, further, that uncertainty determines whether work roles can be formalized or whether they emerge through adaptive and proactive behavior. Cross-classification of task, team member, and organization member behaviors with proficiency, adaptivity, and proactivity produced nine subdimensions of work role performance. Ratings from 491 supervisors from 32 organizations and self-ratings from employees in two organizations (n's = 1,228 and 927) supported the proposed distinctions. Self-reports of proactivity were positively correlated with two external measures of proactivity.